How lymphatic filariasis was eliminated from an urban poor setting in Santo Domingo, Dominican Republic. Issue 2 (4th October 2018) - Gonzales, Manuel; Baker, Margaret C; Celestino, Ana; Santa Morillo, Danerys; Chambliss, Amy; Adams, Sarah; Gyapong, Margaret; Kyelem, Dominique
Abstract: Background: While progress has been made in the elimination of lymphatic filariasis, challenges that call for innovative approaches remain. Program challenges are increasingly observed in 'hard-to-reach' populations: urban dwellers, migrant populations, those living in insecurity, children who are out of school and areas where infrastructure is weak and education levels are low. 'Business-as-usual' approaches are unlikely to work. Tailored solutions are needed if elimination goals are to be reached. This article focuses on mass drug administrations (MDAs) in urban settings. Methods: We selected the urban poor area of Santo Domingo, Dominican Republic. With three rounds of MDA and with good coverage, elimination was achieved. We wanted to understand contributing factors to achieving good coverage. A qualitative study analyzed context, barriers and facilitators using a predefined framework based on review of the literature. Results: Results show that barriers commonly reported in urban settings were present (population density, lack of organization in household layout, population mobility, violence, shortage of human resources and challenges in monitoring treatment coverage). Tactics used included strong visibility in the community leading to high levels of awareness, the use of laminated photo sheets during house-to-house visits and a 1:4 supervision strategy. The importance of working through community leadership structures and building relationships with the community was evident. Discussion: The approach developed here has applications for large-scale treatment programs for lymphatic filariasis and other diseases in urban settings.